Growth Performance Characteristics of Okra (Hibiscus esculentus) using Improvised Drip Irrigation System - Amoo, M.O.; Adedeji, M.A.; Oke, A.M.; Aremu, T.E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Okra is a common and popular vegetable crop used in Nigeria. Irrigation method has very significant influence on okra (Hibiscus esculentus) production. A careful effect of marginal water quality on IDI and control system which were subjected to the same conditions was investigated. An experimental field area of 13.5 m2 by 6.0 m2 was properly cleared, stumped, ploughed, harrowed and leveled. High yielding and disease resistant okra variety seeds were carefully selected and planted at a regular interval of 0.6 m. The results of statistical analysis obtained using Completely Randomized Blocked Design (CRBD) (P˂0.05) revealed that there were significant differences on water application which reflected an increase in some agronomic parameters such as growth, weight, yield and vegetative development of the okra. These selected okra agronomic parameters showed that the okra performed in IDI. Maximum fruit yield of 71.71% and water utilization efficiency of 55.49% was obtained by using IDI system.